Short-term effects of increased temperature and lowered pH on a temperate grazer-seaweed interaction (Littorina obtusata/Ascophyllum nodosum) - Cardoso, Patricia G. (2020)
There has been a significant increase in the literature regarding the effects of warming and acidification on the marine ecosystem. To our knowledge, there is very little information on the potential effects of both combined stressors on marine grazer-seaweed interactions. Here, we evaluated, for the first time several phenotypic responses (e.g periwinkle survival, condition index, consumption rates, seaweed photosynthetic activity and oxidative stress) of the temperate periwinkle Littorina obtusata (grazer) and the brown seaweed Ascophyllum nodosum (prey) to such climate change-related variables, for 15 days. Increased temperature (22 °C, pH 8.0) elicited a significant lethal effect on the periwinkle within a short-term period (mortality rate > 90%). Acidification condition (18 °C, pH 7.6) was the one that showed lower mortality rates (≈20%), reflected by lower impact on periwinkle fitness and consumption rates. Under a scenario of increased temperature and lowered pH the antioxidant defences of L. obtusata seemed to be supressed increasing the risk of peroxidative damage. The seaweed evidenced signs of cellular damage under such conditions. These results suggest that: i) lower pH per se seems to benefit the interaction between grazer and seaweed while, ii) a combined scenario of increased temperature and lowered pH may be negative for the interaction, due to the unbalance between periwinkle mortality rates and consumption rates. But most importantly, since grazing often plays an important role on structuring natural communities, such predator-prey disturbances can elicit cascading effects on the remaining community structure and functioning of the temperate rocky-shore ecosystems.